Peran Edukasi dan Evaluasi Handgrip Strength sebagai Upaya Deteksi Dini Sarcopenia pada Usia Produktif di Cengkareng - Sidarta, Erick; Santoso, Alexander Halim; Destra, Edwin; Wijaya, Bryan Anna; Setiawan, Fiona Valencia (Journal of Community Service and Society Empowerment, 2025)
Hydrated skin is an important indicator of overall skin health, as water content in the stratum corneum plays a vital role in maintaining the skin barrier function. Insufficient hydration can lead to dry skin, increase the risk of infections, and reduce quality of life. This activity aimed to assess skin water and oil levels among the elderly residents at Hana Nursing Home to prevent dry skin conditions. The PDCA (Plan–Do–Check–Act) approach was applied, which included planning the screening activities, measuring skin water and oil levels, evaluating the results, and providing skin care education for participants with abnormal findings. A total of 36 elderly individuals participated in this activity at Hana Nursing Home, South Tangerang. The results showed that 20 participants (55.56%) had low oil levels, while 24 participants (66.67%) had low water levels. These findings underscore the importance of maintaining skin hydration through adequate fluid intake, regular use of moisturizers, and adopting a healthy lifestyle. Early detection of skin hydration status, combined with targeted education, is effective in preventing dry skin and improving quality of life in the elderly population.